Executive Committee Minutes 2006-08-24 - Academic Senate:::::::::
Faculty Eligible for Emeritus Status, Chair Initiatives - Comprehensive 4 unit conversion, Chair Initiative: Lower SFR, Election needed for Search Committee for Vice President for Development, Faculty needed for Periodic Review of Administrators